2020
DOI: 10.2967/jnumed.120.256180
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density: Clinical Relevance and Quantitative Assessment

Abstract: Learning Objectives: On successful completion of this activity, participants should be able to describe (1) the benefits and limitations of evaluating bone mineral density by dual-energy x-ray absorptiometry and FRAX to assess fracture risk; (2) the uses of various pharmacologic therapies available for the treatment of osteoporosis; and (3) the process of monitoring and ensuring patient response to osteoporosis therapy.Financial Disclosure: Dr. Farooki has received consulting fees from Amgen and has been an Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…At baseline assessment, the heel BMD of participants was evaluated by quantitative ultrasound and then converted into a T score. Although dual‐energy x‐ray absorptiometry technology is recognized by the World Health Organization as the gold standard for the diagnosis of osteoporosis, quantitative ultrasound was also widely used in screening because of its low cost, convenience, and high consistency with dual‐energy x‐ray absorptiometry diagnosis in the UK Biobank 17‐19 . The following descriptive categories were proposed according to diagnostic criteria of osteoporosis 20 : T score ≥−2.5, and T score <−2.5, whereas women with T score <−2.5 were further divided into those with or without fractures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At baseline assessment, the heel BMD of participants was evaluated by quantitative ultrasound and then converted into a T score. Although dual‐energy x‐ray absorptiometry technology is recognized by the World Health Organization as the gold standard for the diagnosis of osteoporosis, quantitative ultrasound was also widely used in screening because of its low cost, convenience, and high consistency with dual‐energy x‐ray absorptiometry diagnosis in the UK Biobank 17‐19 . The following descriptive categories were proposed according to diagnostic criteria of osteoporosis 20 : T score ≥−2.5, and T score <−2.5, whereas women with T score <−2.5 were further divided into those with or without fractures.…”
Section: Methodsmentioning
confidence: 99%
“…Although dual-energy x-ray absorptiometry technology is recognized by the World Health Organization as the gold standard for the diagnosis of osteoporosis, quantitative ultrasound was also widely used in screening because of its low cost, convenience, and high consistency with dual-energy x-ray absorptiometry diagnosis in the UK Biobank. [17][18][19] The following descriptive categories were proposed according to diagnostic criteria of osteoporosis 20 : T score ≥−2.5, and T score <−2.5, whereas women with T score <−2.5 were further divided into those with or without fractures. The diagnosis of fracture was obtained through linkage to the inpatient hospitalization data in the UK Biobank using International Classification of Diseases-10 (ICD-10) codes (S02, S12, S22, S32, S42, S52, S62, S72, S82, S92, T02, T12).…”
Section: Bone Mineral Densitymentioning
confidence: 99%
“…The body of evidence available evokes the need to evaluate the benefits of exercise administered to postmenopausal women with OP. To date, the dual-energy X-ray absorptiometry (DXA) for the assessment of bone mineral density (BMD) is the most widely used tool to diagnose and monitor the OP [ 22 , 23 ]. Some blood and urinary biomarkers have been proposed to assess the dynamics of bone metabolism and to evaluate the efficacy of therapeutic interventions for OP [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis (OP) is a complex multifactorial disease, mainly manifested as a decrease in bone density and bone strength, and its diagnosis and quantitative assessment mainly rely on bone density assay [ 1 ]. Recent studies have shown that bone marrow adipose tissue (BMAT) plays an important influence in the mechanism of OP, and its endocrine effect and impact on bone structural strength is worth noting [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%